2000
DOI: 10.3168/jds.s0022-0302(00)75104-6
|View full text |Cite
|
Sign up to set email alerts
|

Separation of Lactoferrin-a and -b from Bovine Colostrum

Abstract: Bovine lactoferrin was separated into lactoferrin-a and lactoferrin-b from bovine colostrum. Lactoferrin-a was eluted at 0.38 M NaCl and lactoferrin-b was eluted at 0.43 M NaCl by carboxymethyl cation-exchange chromatography at pH 7.7, 0.05 M phosphate buffer. The molecular weights were estimated at 84,000 for lactoferrin-a and 80,000 for lactoferrin-b. Lactoferrin-a contents were 258.0 mg/L and lactoferrin-b contents were 524.3 mg/L of colostrum for cow 19. From colostrum to normal milk, total lactoferrin was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
45
1
3

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(50 citation statements)
references
References 12 publications
1
45
1
3
Order By: Relevance
“…Interestingly, the concentration of bLf-a, which has a higher molecular mass than bLf-b, in colostrum is greater than in normal milk. As bLf-a was found to exhibit a stronger bactericidal activity against Escherichia coli than bLf-b, it was suggested that bLf-a may play an important healthy role in colostrum drinking calves (Yoshida et al 2000). Lastly, the presence of mannose-type glycans in bLf molecule has been described to be responsible for its capacity to induce mannose receptor-dependent delayed type hypersensitivity (DTH) response to ovalbumin (OVA) in mice Zimecki et al 2002).…”
Section: Role Of Glycosylation In the Regulation Of Lps-induced Immunmentioning
confidence: 97%
“…Interestingly, the concentration of bLf-a, which has a higher molecular mass than bLf-b, in colostrum is greater than in normal milk. As bLf-a was found to exhibit a stronger bactericidal activity against Escherichia coli than bLf-b, it was suggested that bLf-a may play an important healthy role in colostrum drinking calves (Yoshida et al 2000). Lastly, the presence of mannose-type glycans in bLf molecule has been described to be responsible for its capacity to induce mannose receptor-dependent delayed type hypersensitivity (DTH) response to ovalbumin (OVA) in mice Zimecki et al 2002).…”
Section: Role Of Glycosylation In the Regulation Of Lps-induced Immunmentioning
confidence: 97%
“…Human LF consists of 691 amino acids and contains 3 potential glycosylation sites at Asn138, Asn479, and Asn624; Asn138 and Asn479 are occupied with complex-type N-glycans, whereas Asn624 is usually unoccupied [25,26]. Bovine LF consists of 689 amino acids and has 5 potential glycosylation sites at Asn233, Asn288, Asn368, Asn476, and Asn545; Asn233, Asn368, Asn467, and Asn545 are always occupied, and Asn288 is occupied for about 30% [18,19,27].…”
mentioning
confidence: 99%
“…Essas observações estão de acordo com os estudos anteriores que referiram à maior concentração de lactoferrina no colostro e diminuição na sua concentração com o evoluir dos dias de lactação para vacas (SANCHEZ et al, 1988;TSUJI et al, 1990;HENG, 1999;YOSHIDA et al, 2000;BAROZA, 2007;HISS;MEYER;SAUERWEIN, 2008;ROCHA et al, 2009) e cabras (SANCHEZ et al, 1988;TSUJI et al, 1990;HENG, 1999;YOSHIDA et al, 2000; Resultados e discussão Raimondo, R. F. S. HISS;MEYER;SAUERWEIN, 2008;ROCHA et al, 2009). …”
Section: Resultsunclassified
“…Na literatura compulsada há discrepância nos valores de lactoferrina encontrados no colostro possivelmente devido as diferentes técnicas utilizadas (TSUJI et al, 1990;YOSHIDA et al, 2000). No estudo das proteínas do colostro de cabras através da técnica de eletroforese SDS-PAGE, Baroza (2007) observou diminuição da concentração de lactoferrina durante o 1º mês de lactação, pois os valores máximos obtidos no dia do parto iguais a 396 ± 78 mg/dL diminuíram abruptamente no 1º dia de lactação (98,3…”
Section: Avaliação Da Influência Do Período Colostral E Do Primeiro Munclassified
See 1 more Smart Citation